Fashionable childhood children in advertising - Vanska, Annamari (Bloomsbury, 2017)
"Fashionable Childhood is the first book to critically examine representations of children and childhood through fashion media. Focussing on themes such as innocence, sexuality, class, and gender, this book provides a detailed and fascinating overview of the topic over the last 40 years"--Provided by publisher.